PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN - Putri, Dwi Kartika (Management Analysis Journal, 2014)
The objective of the study is to analyze the good effects of product and service quality to the customers loyalty Shop. The population of this study was shop customers Lima Jaya Shop, Pekalongan as much 100 respondents using Proportionate Random Sanpling method. The method used in collecting the data was a questionnaire which was measured by liker scale. Based on the partial test, direct influence of product quality to customer loyalty is 0,020 and direct influence of service quality to customer loyalty is 0,002. This study concludes that there  is  product  quality  and  service  quality  are  positive  and  significant  partially  store  customer  loyalty. Manajerial implications for the store should have to improve the low dimensional as product durability and conformance of products by providing quality product that include material qualification, theoretical implications of further research are expected to examine other variables such as the belief that it is possible to have a variable effect on customer loyalty.